Domestic violence in international context - Scharff Peterson, Diana; Schroeder, Julie A. (Routledge studies in crime and society, 2017)
Introduction: international response to domestic violence / Julie Schroeder, Diana Bruns, Olga Osby and Safiya Omari -- Intimate partner violence in Canada : policies, practices, and prevalence / Darryl Plecas, Irwin Cohen and A. McCormick -- The prevalence of severe intimate partner violence in Sweden / Susanne Strand and Heidi Selenius -- Responding to domestic abuse in England and Wales / Stephanie L. Reardon and Kim Trevillion, on behalf of Limeculture -- Levels of prevention of intimate partner violence against women analyzed from the multi-causal-ecological pyramidal model : the case of Spain / Victoria A. Ferrer-Perez andEperanza Bosch-Fiol -- Domestic violence in Italy : an epidemic phenomenon / Bruno Meini -- Domestic violence in Austria / Maximilian Edelbacher and Josef Horl -- Domestic violence in Turkey : unreported cases and civic/state response / Ozgur Solakoglu, M. Tugba Erdem, Suhey Gurbuz and Eray Karlidag -- Status quo and countermeasures on domestic violence in Japan / Susumu Nagai -- The Vietnamese police response to domestic violence against women : the family unit under pressure / Mike Perkins, Louise Cotrel-Gibbons and Huong Thu Nguyen -- Domestic violence in Australia : a wicked problem / Sedat Mulayim and Miranda Lai -- Domestic violence in South Africa : an unpleasant narrative / Christiaan Bezuidenhout -- Combatting the menace of domestic violence : the Ghanaian experience / Gerald Depaah Gyamfi